Therapeutic gymnastics and pelotherapy in physical rehabilitation of patients after arthroscopic surgery on the shoulder joint - A. V. Mikhaleva; A. G. Kulikov; I. N. Makarova; A. V. Doktorov; E. E. Pakhomova (National Electronic Information Consortium (NEICON), 2020)
Objective: to improve the effectiveness of early postoperative rehabilitation of patients after arthroscopic surgery on the shoulder joint by the combined use of exercises with dynamic controlled muscle tension (DCMT) and thin-layer peloidotherapy. Materials and methods: 98 patients operated on for rotator cuff syndrome, were divided into 3 groups, comparable in age, sex and the main clinical manifestations. All patients received basic therapy, including orthopedic mode in the form of immobilization of the upper limb and curative gymnastics according to the standard method. Patients of the I and II group in addition to basic treatment were given an exercise course with dynamic controlled muscle tension during the immobilization and postimmobilization period. Patients of the II main group in the postimmobilization period received pelotherapy. Results: according to the results of goniometry in patients of I and II groups had the greater volume of movement in the shoulder joint after immobilization was stopped in comparison with patients of group III (control). Analysis of pain indicators while the shoulder joint moving on the scale of pain a month after immobilization revealed a significant advantage of the results of the II main group. Conclusions: it was shown that the inclusion of exercises with dynamic controlled muscle tension in the therapeutic complex had a more significant effect on the main clinical symptoms of the disease, the regeneration processes, and also contributed to an earlier restoration of impaired functions of the shoulder joint.